Absence of leukaemic fusion gene transcripts in preterm infants exposed to diagnostic x rays. Issue 3 (1st May 2003) - Ravetto, P F; Agarwal, R; Chiswick, M L; D'Souza, S W; Eden, O B; Taylor, G M
Abstract : Background: Childhood leukaemias express novel, clonotypic fusion genes that may already be present at birth before the clinical manifestation of leukaemia. Exposure of the fetus to diagnostic x rays is reported to increase the risk of childhood leukaemia, and may do so by generating leukaemic fusion genes. Advances in neonatal medicine in the past decade that have extended the limits of viability of preterm babies down to 23 weeks of gestation have resulted in the increased use of diagnostic x rays to monitor neonatal progress. Aim: To investigate whether exposure of very preterm infants to diagnostic x rays in the neonatal period leads to the development of leukaemic fusion genes. Methods: Peripheral blood samples were collected at birth from very preterm infants (23–30 weeks gestation) and following exposure to diagnostic x rays at intervals of two weeks, until discharge. Cord blood samples from normal full term infants served as controls. Total RNA was extracted from the blood and the expression of the fusion genes TEL-AML1, MLL-AF4, and BCR-ABL, characteristic of three subtypes of childhood leukaemia, was investigated in the preterm and full term infant samples using a nested reverse transcriptase polymerase chain reaction method. Serial pre- and post- x ray samples from 42 preterm babies, pre- x ray samples from an additional 46 preterm infants, and cord blood samples from 100 normal full term infants were screened for fusion gene transcripts. Results: No leukaemic fusion gene transcripts were detected in preterm infants following exposure to diagnostic x rays. A BCR-ABL transcript was identified in a single preterm infant prior to x ray exposure. TEL-AML1 transcripts were detected in cord blood samples from two full term infants. MLL-AF4 transcripts were not detected in any of the pre- or full term infants tested. Conclusions: Exposure of the preterm infants to x rays in this small series and at the doses used for diagnostic purposes did not induce leukaemic fusion gene expression, but we cannot exclude the possibility that a small proportion of preterm infants may be unusually sensitive to x rays.